2016
DOI: 10.1021/jacs.5b12703
|View full text |Cite
|
Sign up to set email alerts
|

AMHB: (Anti)aromaticity-Modulated Hydrogen Bonding

Abstract: This in silico survey shows that changes in the (anti)aromatic character of π-conjugated heterocycles can be used to fine-tune their hydrogen (H-)bond strengths. Upon H-bonding dimerization, the π-electrons of these rings can be polarized to reinforce or disrupt their (anti)aromatic π-conjugated circuits (πCCs) and stabilize or destabilize the resulting H-bonded complexes. H-bonding interactions that enhance aromaticity or relieve antiaromaticity are fortified, whereas those that intensify antiaromaticity or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…104 They reported that hydrogen bonds are stronger than expected when they increase [4n + 2] cyclic π-electron delocalization (aromaticity gain) in the hydrogen bonding compounds, and are weaker than expected when they decrease [4n + 2] cyclic π-electron delocalization (aromaticity loss) in compounds (Figure 13a). Later works from Wu and Jackson et al 105,106 extended the original idea to show that the opposite happens for [4n] "antiaromatic" rings, and these reciprocal relationships were later applied to rationalize the trends of hydrogen bonding in self-assembling systems, 80,[107][108][109] in multipoint arrays, 78,79 and may rationalize short, strong hydrogen bonds in enzymes. 110 Whether light irradiation strengthens or weakens a hydrogen bond also can be related to changes in (anti)aromaticity of hydrogen bonding compounds in the excited state.…”
Section: Aromaticity and Antiaromaticitymentioning
confidence: 99%
“…104 They reported that hydrogen bonds are stronger than expected when they increase [4n + 2] cyclic π-electron delocalization (aromaticity gain) in the hydrogen bonding compounds, and are weaker than expected when they decrease [4n + 2] cyclic π-electron delocalization (aromaticity loss) in compounds (Figure 13a). Later works from Wu and Jackson et al 105,106 extended the original idea to show that the opposite happens for [4n] "antiaromatic" rings, and these reciprocal relationships were later applied to rationalize the trends of hydrogen bonding in self-assembling systems, 80,[107][108][109] in multipoint arrays, 78,79 and may rationalize short, strong hydrogen bonds in enzymes. 110 Whether light irradiation strengthens or weakens a hydrogen bond also can be related to changes in (anti)aromaticity of hydrogen bonding compounds in the excited state.…”
Section: Aromaticity and Antiaromaticitymentioning
confidence: 99%
“…67 Presumably, this effect can be analysed theoretically. 68 The data for homodimers of a, h, and e will fit the observed correlation better if their gas-phase PA will be increased by 15 kJ/mol. Thus, the attenuation of the proton affinity for these homodimers is smaller than for similar species.…”
mentioning
confidence: 92%
“…[14] Thep osition of the conformational equilibrium in these new balances enables measurement of the energy of the Hbond at the end of alinear chain of one,two,orthree Hbonds.These molecular balances were synthesized and found to exist in two conformational states on the NMR timescale at room temperature (see the Supporting Information for NMR spectra and minimized structures). Conformers were assigned using 2D NMR spectroscopy and the equilibrium constant K was determined by integration of the 19 FNMR peaks corresponding to each conformer. Thed ifference in the Gibbs energy between the conformers was determined using DG = ÀRT lnK.…”
mentioning
confidence: 99%